UTILIZATION OF BAGASSE ASH FOR THE PREPARATION OF SILICA AEROGEL/MgO COMPOSITES THROUGH AMBIENT-PRESSURE DRYING - Azhar, Istighfarin Meilidya; Nazriati, Nazriati; Kusumaningrum, Irma Kartika (Walisongo Journal of Chemistry, 2025)
This study presents the preparation of silica aerogel/MgO composites using bagasse ash as a silica source and MgCl₂·6H₂O as the MgO precursor. Sodium silicate was extracted from bagasse ash and converted into silicic acid through ion-exchange treatment. Silica aerogel formation was achieved through gelation, followed by surface modification using TMCS and HMDS. Magnesium oxide was incorporated via co-precipitation with MgCl₂·6H₂O and subsequently stabilized through calcination. The composites were characterized using FTIR, XRD, and BET–BJH analyses. XRD results revealed a hybrid amorphous–crystalline structure, with silica predominantly in the amorphous phase and MgO in the crystalline phase. BET analysis showed a pore volume of 0.50 cm³/g and a specific surface area of 121.99 m²/g, while the pore-size distribution confirmed its mesoporous nature. FTIR spectra indicated the presence of functional groups corresponding to Si–O–Si, Si–C, C–H, and Mg–O, confirming the successful integration of MgO into the silica aerogel framework. These findings demonstrate the successful preparation of silica aerogel/MgO composites from bagasse ash under ambient-pressure drying conditions.